Quick-charge type composite negative pole piece, preparation method and lithium ion battery

By adopting a multi-layer composite structure, the combination of graphite materials and conductive agents of different particle sizes is solved, and the balance between fast charging performance and energy density of lithium-ion batteries is achieved, and the high-speed fast charging and cycling performance is improved, ensuring the safety and energy density of the battery.

CN119581486APending Publication Date: 2025-03-07HUNAN LEAD POWER TECH GRP CO LTD +2

Patent Information

Application Number
CN202411701656.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to ensure its energy density while improving the fast charging performance of lithium-ion batteries. In addition, the insufficient lithium-embedding capability of the negative electrode material in the fast charging mode may lead to lithium-ion excision phenomenon, lithium dendrites and other problems, affecting battery life and safety.

Method used

The fast charging negative electrode sheet with a multi-layer composite structure, including a current collector layer, a first active material coating and a second active material coating, is designed with low loading and high loading formulas through the combination of graphite materials of different particle sizes, to build a dense conductive network to improve the conductivity and energy density of the battery.

Benefits of technology

The battery's high-rate fast charging performance and cycle performance is improved, the risk of negative electrode lithium extraction is reduced, and the energy density and safety of the battery are ensured. The peak charging rate can reach 6C, the average charging rate is about 4C, and the time for charging 5% to 80% SOC does not exceed 12min.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581486A_ABST
    Figure CN119581486A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy batteries, in particular to a quick-charge type negative pole piece, a preparation method and a lithium ion battery. The quick-charging type composite negative pole piece comprises a current collector layer, the first active material coating layer is coated on the current collector layer; the second active material coating layer is coated on the first active material coating layer; wherein the particle size of the graphite material of the first active material coating is larger than that of the graphite material of the second active material coating. The dynamic performance of the negative plate can be effectively guaranteed, the infiltration effect and the rate charging performance of the battery are improved, the risk of lithium precipitation of the negative electrode is reduced, and the rate fast charging performance of the battery is improved through the multi-layer microstructure design of the battery pole plate without changing the material type.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy batteries, and in particular to a fast-charging negative electrode plate and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] There are usually two ways to reduce the charging time of lithium-ion batteries in electric vehicles: 1) One is to shorten the time required for charging by increasing the charging speed, which is also the strategy adopted by most new energy vehicles at present; 2) The second is to quickly replace the empty battery pack with a fully charged battery pack by replacing the battery pack.

[0003] Although increasing the charging speed can effectively shorten the charging time, too high a charging speed will also accelerate the battery degradation rate, affecting the service life of electric vehicles. At present, ordinary commercial lithium-ion batteries can also be occasionally charged and discharged at a high rate, but long-term high-rate charging and discharging will lead to increased battery failure. Fast-charging lithium-ion batteries require professional fast-charging material selection, battery design and charging methods to achieve the ideal fast-charging effect.

[0004] Negative electrode materials are a key factor in fast charging technology. In fast charging mode, lithium ions are instantly released from the inside of the positive electrode material and migrate to embed into the negative electrode. The negative electrode needs to have a very high lithium insertion capacity, otherwise lithium precipitation may occur and lithium dendrites may be generated, resulting in a decrease in battery life or even a short circuit, causing safety problems. The battery surface density and compaction density have a significant impact on the battery's rate, cycle and other performance. Fast-charging lithium-ion batteries require a low surface density design, and too high or too low compaction density will lead to poor performance. If the compaction density is too high, the active material of the pole piece will be "crushed to death", causing its cycle capacity to drop rapidly, while the compaction density is too low, resulting in insufficient contact between its active materials, and the impedance of the battery is large, resulting in poor fast charging performance. Improving the fast charging performance of the battery through pole piece structure design, especially the use of multi-layer coating technology to form a multi-gradient, multi-porous structure, is the mainstream means to improve the ion transmission rate of the negative electrode material. Therefore, the selection of negative electrode materials must have corresponding kinetic properties, and the energy density of the battery must also be guaranteed.

[0005] Constant current constant voltage charging (CC-CV) is the most traditional charging method. This method first uses a suitable current for constant current charging. After reaching the cut-off voltage, it switches to constant voltage charging and continuously reduces the charging current to minimize the polarization of the battery. For this traditional charging method, the most effective way to shorten the charging time is to increase the charging current. However, increasing the charging current will increase the polarization and prolong the constant voltage charging time. On the other hand, high current charging will also cause lithium deposition at the negative electrode. Therefore, it is also very important to adopt a suitable charging strategy for fast charging.

[0006] In the prior art, for example, the invention patent CN 113948708 B can form a dense conductive network structure by introducing lithium manganese oxide and modified white carbon black, ensuring that each part of the negative electrode material inside the battery is charged at the same time, thereby increasing the charging speed and preventing the collapse of the negative electrode active material during the cycle. However, this solution requires lithium manganese oxide and white carbon black to be pre-treated, which increases the BOM cost of the entire battery. At the same time, the introduction of other additive materials aggravates the side reactions of the electrolyte, which is not conducive to the safety of the battery; the invention patent CN 116315036A combines the carbon-coated graphite material raw material with a specific pole piece process to reduce the lithium precipitation at the negative electrode interface at high battery rates, thereby improving the fast charging capability and cycle performance. However, this solution only demonstrates 2C rate charging, and a single pole piece structure is difficult to achieve a higher rate charging capability; Patent CN 218887229 U uses a graphite layer, a carbon material layer and a silicon-based material-lithium-philic metal composite layer coated in sequence on the surface of the current collector, and cooperates with the gradual increase of D50 in each layer. The conductivity gradually decreases from the current collector to the outside, which is beneficial to the outward transmission of electrons, thereby improving the electronic conductivity and ion conductivity of the negative electrode plate. The overall reaction speed of the negative electrode plate with lithium, but this solution requires high process maturity and the process control is relatively cumbersome. It does not utilize large-scale production and also increases the corresponding manufacturing cost.

[0007] To sum up, how to improve the fast charging performance of batteries and ensure their energy density has become a technical problem that needs to be urgently solved in the new energy vehicle industry. Summary of the invention

[0008] The main purpose of the present invention is to provide a fast-charging negative electrode plate and a preparation method, and a lithium-ion battery to solve the above-mentioned technical problems.

[0009] To achieve the above object, the present invention provides a fast-charging composite negative electrode sheet, comprising:

[0010] a current collector layer;

[0011] a first active material coating applied on the current collector layer;

[0012] a second active material coating applied on the first active material coating;

[0013] Wherein, the particle size of the graphite material of the first active material coating is greater than the particle size of the graphite material of the second active material coating.

[0014] Furthermore, the graphite material of the first active material coating is a mixture of single particles of needle coke with a D50 of 10 to 14 um and secondary particles of petroleum coke with a D50 of 12 to 16 um, with a mixing ratio of 20 to 50%: 80 to 50%; the graphite material of the second active material coating is a secondary particle material of petroleum coke with a D50 of 14 to 20 um.

[0015] Furthermore, the first active material coating has a pole piece porosity of 20% to 35%, and the second active material coating has a pole piece porosity of 25% to 45%.

[0016] Furthermore, the mass ratio of the first active material coating layer to the second active material coating layer is 10-90%:90-10%.

[0017] Furthermore, the first active material coating and the second active material coating also include acetylene black conductive agent and a binder.

[0018] The present invention also provides a method for preparing the fast-charging composite negative electrode sheet as described in any one of the above items, comprising the steps of:

[0019] S1, according to the first active material coating of graphite material: acetylene black conductive agent: binder: thickener = 92-97.5%: 0.5-2.0%: 0.8-2.8%: 1.2-3.2%, firstly, the graphite material, the conductive agent acetylene black and the binder are mixed and stirred sufficiently, then a solvent is added to a solid content of 68%-74% and kneaded, and the solvent is gradually added and stirred until the slurry viscosity meets 2000-6000mP·s, and a thickener is added and stirred quickly to obtain a first active material coating slurry with a slurry solid content of about 45%-52%;

[0020] S2, according to the second active material coating of graphite material: acetylene black conductive agent: binder: thickener = 92-97.5%: 0.5-2.0%: 0.8-2.8%: 1.2-3.2%, firstly, the graphite material, conductive agent acetylene black and binder powder are mixed and stirred thoroughly, then the solvent is added to the solid content of 68%-74% and kneaded, the solvent is gradually added and stirred until the slurry viscosity meets 2000-6000mP·s, and the thickener is added and stirred quickly to obtain a second active material coating slurry with a slurry solid content of about 50-60%;

[0021] S3, coating the first active material coating slurry on the current collector through a double coating die head device, coating the second active material coating slurry on the first active material coating formed after drying the first active material coating slurry after baking, and rolling it after drying to obtain the fast-charging composite negative electrode plate.

[0022] Furthermore, the surface density of the fast-charging composite negative electrode is designed to be in the range of 160 to 250 g / m 2 After roller pressing, the surface density is 1.45~1.65g / cm 3 .

[0023] Furthermore, the binder is CMC powder, and the thickener is SBR.

[0024] The present invention also provides a lithium-ion battery, comprising the fast-charging composite negative electrode plate as described in any one of the above items.

[0025] Furthermore, the excess ratio of the fast-charging composite negative electrode plate is 5% to 25%.

[0026] The present invention has at least the following beneficial effects:

[0027] 1) Using large-particle high-density mixed graphite material as the first active material coating can effectively ensure the liquid retention performance of the electrode, thereby improving the energy density and cycle performance of the battery. Using small-particle secondary particle graphite material as the second active material coating can effectively ensure the dynamic performance of the negative electrode, improve the infiltration effect and rate charging performance of the battery, and reduce the risk of negative electrode lithium plating. The multi-layer microstructure design of the battery electrode does not need to change the material type to improve the rate fast charging performance of the battery;

[0028] 2) By introducing a multi-layer composite structure, the first active material layer is designed with a low-loading formula, and the high proportion of conductive agent can build a complete and dense conductive network inside the pole piece, greatly enhancing the conductive performance of the pole piece; the second active material layer is designed with a high-loading formula. Since the small-size secondary particle material itself has good conductive / ion conductive properties, the high-loading design can improve the capacity of the battery and ensure the overall energy density of the battery; at the same time, the use of dry kneading process for homogenization and double coating die head technology for coating roller pressing can reduce the electron transmission resistance, greatly improve production efficiency, shorten process cycle, and reduce comprehensive costs;

[0029] 3) Without adjusting the type and proportion of active materials, by differentiating the raw materials and formulas of different coatings and combining them with a specific preparation process, the migration and diffusion rate of lithium ions in the pole piece are improved, concentration polarization is reduced, and its cycle performance and rate performance are improved. Step-charge is used for high-rate charging, the peak charging rate can reach 6C, the average charging rate is about 4C, and the charging time from 5% to 80% SOC does not exceed 12 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:

[0031] Figure 1 It is a schematic diagram of the process of preparing the fast-charging composite negative electrode sheet in the present invention.

[0032] Figure 2 It is a schematic diagram of an enlarged cross section of the fast-charging composite negative electrode plate of the present invention.

[0033] Figure 3 6C fast charging process step curve diagram of Example 4 of the present invention.

[0034] Figure 4 Fully charged disassembly interface diagram after fast charging cycle of Example 4 of the present invention and Comparative Example 3.

[0035] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0036] The following is a clear and complete description of the technical problems solved by the embodiments of the present invention, the technical solutions adopted, and the technical effects achieved in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other equivalent or obviously modified embodiments obtained by ordinary technicians in this field without creative work fall within the scope of protection of the present invention. The embodiments of the present invention can be concretized in a variety of different ways as defined and covered in the claims.

[0037] It should be noted that in the following description, many specific details are given for ease of understanding, but it is obvious that the present invention can be implemented without these specific details.

[0038] It should be noted that, in the absence of clear limitation or conflict, the various embodiments of the present invention and the technical features therein can be combined with each other to form a technical solution.

[0039] Please combine Figure 1 and Figure 4 The experimental steps for manufacturing the fast-charging composite negative electrode plate, assembling the battery, and testing the electrical performance provided in this embodiment are as follows:

[0040] According to the first active material coating, the graphite material, the conductive agent acetylene black, the binder CMC, and the thickener SBR are mixed and stirred thoroughly, and then the solvent is added to a solid content of 68% to 74% for kneading, and the solvent is gradually added and stirred until the slurry viscosity meets 2000 to 6000 mP·s, and the thickener is added and stirred quickly to obtain a first active material coating slurry with a slurry solid content of about 45% to 52%; single-particle artificial graphite of needle coke type with a particle size D50 of 10 to 14 um and secondary particle artificial graphite of petroleum coke type with a particle size D50 of 12 to 16 um are selected, and the ratio of 20 to 50%: 80% to 50% is mixed as the graphite material of the first active material coating.

[0041] According to the second active material coating, the graphite material: acetylene black conductive agent: binder CMC: thickener SBR = 92-97.5%: 0.5-2.0%: 0.8-2.8%: 1.2-3.2%, firstly, the graphite material, conductive agent acetylene black and binder powder are mixed and stirred thoroughly, then the solvent is added to the solid content of 68%-74% for kneading, the solvent is gradually added and stirred until the slurry viscosity meets 2000-6000mP·s, the thickener is added and stirred quickly to obtain a second active material coating slurry with a slurry solid content of about 50-60%; petroleum coke secondary particle artificial graphite with a particle size D50 of 14-20um is selected as the graphite material of the second active material coating.

[0042] The first active material coating slurry is coated on the current collector by a double coating die head device. The process controls the pole piece porosity of the first active material coating to be 20% to 35%. After baking, the second active material coating slurry is coated on the first active material coating formed after the first active material coating slurry is dried. The process controls the pole piece porosity of the second active material coating to be 25% to 45%. The pole piece surface density is designed to be in the range of 160 to 250 g / m2. After drying, roller pressing is performed to obtain a surface density of 1.45 to 1.65 g / cm 3 The fast-charging composite negative electrode plate.

[0043] The prepared fast-charging composite negative electrode sheet is die-cut and then stacked and assembled with the diaphragm material and the positive electrode sheet material in the order of negative electrode + diaphragm + positive electrode + diaphragm, wherein the excess ratio of the negative electrode sheet is 5% to 25% ((excess ratio of the negative electrode sheet = theoretical capacity of the negative electrode sheet - theoretical capacity of the positive electrode sheet) / theoretical capacity of the positive electrode sheet). The stacked naked battery cell is packaged in an aluminum-plastic shell for liquid injection with a liquid injection coefficient of 4.2Ah / g. After packaging, it is formed, aged, and divided into different capacities to prepare a soft-pack battery with a capacity of 5Ah for electrochemical testing.

[0044] Slurry viscosity test: Take the slurry sample from a clean beaker, select a suitable rotor model, set the rotor parameters, immerse the rotor head in the slurry to start the test, and record the results and display the data.

[0045] Pole piece porosity test: punch out 20 14mm small discs from the composite pole piece, use a true density meter to test their true volume, calculate their average value, and then calculate their porosity based on the apparent volume; where porosity = (apparent volume - true volume) / apparent volume * 100%.

[0046] Preparation of positive electrode sheet: Using positive electrode lithium iron phosphate as the active material, according to 97.0% lithium iron phosphate, 0.5% CNT slurry, 1.0% conductive carbon black, 1.5% polyvinylidene fluoride, add N-methylpyrrolidone to homogenize and adjust the viscosity, and then prepare the required positive electrode sheet after coating, baking, rolling and die-cutting.

[0047] Diaphragm: The diaphragm of the embodiment of the present invention is a conventional diaphragm in the art. The diaphragm substrate of the embodiment uses wet-process polyethylene / polypropylene, and the base film thickness is 9um, wherein one side of the diaphragm is coated with a 2um ceramic layer + a 1um PVDF layer.

[0048] Electrolyte: The electrolyte of the embodiment of the present invention is a conventional electrolyte in the art, including an organic solvent, an additive and an electrolyte salt, specifically including 8.7% LiPF6, 3.5% LiFSI, 22% EC, 24% EMC, 37% DMC, 3% VC, 1% FEC, 0.5% DTD, and 0.3% TMSP.

[0049] Electrochemical testing:

[0050] (1) Initial capacity utilization

[0051] Using Shenzhen Xinwei test system, at 25℃, charge to 3.65V at 0.5C constant current and constant voltage, and let it stand for 30min; discharge to 2.5V at 0.5C constant current, and let it stand for 30min; record the charge and discharge capacity, charge and discharge efficiency, discharge constant current ratio and discharge platform voltage during the battery cycle.

[0052] (2) Rate charging test

[0053] Shenzhen Xinwei test system was used to charge the battery to 3.65V at different rates (maximum rates include 2.0C, 3.0C, 4.0C, 5.0C and 6.0C, etc.) at 25°C, and then let it stand for 30 minutes. The battery was discharged at a constant current rate of 1.0C to 2.5V and left to stand for min. The battery was then charged to 3.65V at the same rate. The battery was removed for full-charge interface disassembly to observe whether there were any abnormalities such as black spots and lithium precipitation on the surface of the negative electrode.

[0054] (3) Cycle capacity retention rate

[0055] Using Shenzhen Xinwei test system, at 25℃, cycle test was carried out in the above-mentioned step charging method. The first cycle discharge capacity was recorded as initial capacity C0, the nth cycle discharge capacity was recorded as capacity Cn, and the ratio of Cn to C0 was the capacity retention rate of the current number of cycles.

[0056] The following table shows the specific component design and process parameters of Examples 1-5 and Comparative Examples 1-3 provided in this application:

[0057] Table 1 Specific component design and process parameters of Examples 1-5 and Comparative Examples 1-3

[0058]

[0059] Please refer to Figure 2-4 , and Table 2 Comparison of test data of Examples 1-5 and Comparative Examples 1-3, Figure 2 The structural diagram in the figure shows that the electrode has two material coatings with different particle sizes and pore distributions, where the first coating is a mixture of single crystal particles and secondary particles, and the second coating is a pure secondary particle material. Figure 3 From the fast charging process curve, we can see that the peak rate of battery charging reaches 6C (30A), the charging time of 5% to 80% SOC is 12 minutes, and the average rate charging rate is about 4C. Figure 4 From the fully charged disassembly interface diagram, it was found that the fully charged interface of the negative electrode of Example 4 was golden yellow as a whole, without any abnormalities such as black spots of lithium deposition, while the fully charged interface of the negative electrode of Comparative Example 3 had large areas of black spots of lithium deposition, indicating that Example 4 can achieve a fast charging effect.

[0060] Table 2 Comparison of test data of Examples 1-5 and Comparative Examples 1-3

[0061]

[0062] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.

Claims

1. A fast-charging composite negative electrode plate, characterized in that: include: a current collector layer; a first active material coating applied on the current collector layer; a second active material coating applied on the first active material coating; Wherein, the particle size of the graphite material of the first active material coating is greater than the particle size of the graphite material of the second active material coating.

2. The fast-charging composite negative electrode plate according to claim 1, characterized in that: The graphite material of the first active material coating is a mixture of single particles of needle coke with a D50 of 10 to 14 um and secondary particles of petroleum coke with a D50 of 12 to 16 um, with a mixing ratio of 20 to 50%: 80 to 50%; the graphite material of the second active material coating is a secondary particle material of petroleum coke with a D50 of 14 to 20 um.

3. The fast-charging composite negative electrode plate according to claim 1, characterized in that: The pole piece porosity of the first active material coating is 20% to 35%, and the pole piece porosity of the second active material coating is 25% to 45%.

4. The fast-charging composite negative electrode sheet according to claim 1, characterized in that: The mass ratio of the first active material coating layer to the second active material coating layer is 10-90%:90-10%.

5. The fast-charging composite negative electrode plate according to claim 1, characterized in that: The first active material coating layer and the second active material coating layer further include acetylene black conductive agent and a binder.

6. A method for preparing a fast-charging composite negative electrode sheet according to any one of claims 1 to 5, characterized in that: Includes steps: S1, according to the first active material coating of graphite material: acetylene black conductive agent: binder: thickener = 92-97.5%: 0.5-2.0%: 0.8-2.8%: 1.2-3.2%, firstly, the graphite material, the conductive agent acetylene black and the binder are mixed and stirred sufficiently, then a solvent is added to a solid content of 68%-74% and kneaded, and the solvent is gradually added and stirred until the slurry viscosity meets 2000-6000mP·s, and a thickener is added and stirred quickly to obtain a first active material coating slurry with a slurry solid content of about 45%-52%; S2, according to the second active material coating of graphite material: acetylene black conductive agent: binder: thickener = 92-97.5%: 0.5-2.0%: 0.8-2.8%: 1.2-3.2%, firstly, the graphite material, conductive agent acetylene black and binder powder are mixed and stirred thoroughly, then the solvent is added to the solid content of 68%-74% and kneaded, the solvent is gradually added and stirred until the slurry viscosity meets 2000-6000mP·s, and the thickener is added and stirred quickly to obtain a second active material coating slurry with a slurry solid content of about 50-60%; S3, coating the first active material coating slurry on the current collector through a double coating die head device, coating the second active material coating slurry on the first active material coating formed after drying the first active material coating slurry after baking, and rolling it after drying to obtain the fast-charging composite negative electrode plate.

7. The method for preparing the fast-charging composite negative electrode sheet according to claim 6, characterized in that: The surface density of the fast-charging composite negative electrode is designed to be in the range of 160 to 250 g / m 2 After roller pressing, the surface density is 1.45~1.65g / cm 3 .

8. The method for preparing the fast-charging composite negative electrode sheet according to claim 6, characterized in that: The binder is CMC powder, and the thickener is SBR.

9. A lithium ion battery, characterized in that: It comprises a fast-charging composite negative electrode sheet as described in any one of claims 1 to 5.

10. The method for preparing a fast-charging composite negative electrode sheet according to claim 6, characterized in that: The excess ratio of the fast-charging composite negative electrode plate is 5% to 25%.

Citation Information

Patent Citations

  • Quick-charge type lithium ion battery and preparation method thereof

    CN116315036A

Cited By

  • Negative plate, preparation method of negative plate and battery

    CN121123163A